Tolerance and Efficacy of Interferon-alpha in Hemodialysis Patients in Tripoli - Buargub Mahdia; El Huni Suheir; Tagdi Moh′d (Saudi Journal of Kidney Diseases and Transplantation, 2006)
A prospective non-randomized study was conducted at the Department of Infectious Diseases at Tripoli Medical Center. We evaluated the tolerance and efficacy of interferon-alpha (IFN) monotherapy in our hemodialysis (HD) patients with chronic hepatitis C virus (HCV) infection. Patients with evidence of active viral infection i.e. positive polymerase chain reaction (PCR) results and who were potential transplant candidates were included in the study. They received three million units of IFN-alpha, administered subcutaneously, three times a week for 12 months. The treatment was discontinued in 12 out of the 35 treated patients (i.e drop out rate 34.2%). Among the 23 patients who completed the treatment course, 14 (60.8%) became PCR negative, and by the end of eighteen months, nine of the patients maintained PCR negativity (39%). Thus, a sustained virological response was observed in nine (25.7%) of the 35 enrolled patients. Our study suggests that the efficacy of IFN-alpha in our patients was less than anticipated and the tolerance to the drug was poor. However, studies involving larger numbers of patients are required to optimize the treatment protocol.